The Effect of Using Blended Learning on the Learning Outcomes of Medan State University Business Education Students - Henny Grace Enjel N. Waruwu; Silvia A.P. Sigalingging; Joseph Raja Sihite; Jane Olivia Theresia; Dimas Sakti; Gerald Nick Emmanuel; Dionisius Sihombing; Asmin (Outline Journal of Education, 2025)
This research aims to analyze the effect of implementing blended learning on the learning outcomes of Medan State University Business Education students. Using quantitative descriptive methods, this research involved 30 students as respondents who were selected using purposive sampling. Data was collected through a questionnaire with a Likert scale and analyzed using a simple linear regression test. The research results show that the application of blended learning does not have a significant influence on student learning outcomes, with an R value of 0.231 and an R Square of 5.3%, which means that only 5.3% of the variation in learning outcomes can be explained by blended learning. The calculated T value (-1.256) is also smaller than the T table (2.048) with a significance level of 0.220 (> 0.05). This conclusion indicates that student learning outcomes are more influenced by other factors outside the variables of this research.